Extraction of fluorapatite from brachiopads for use as a dental material - Sze, Kyle T.; Liberato, Astrid Ayla E.
Hydroxyapatite and carbonated hydroxyapatite have been commonly used for orthopedic and dental applications because their composition is similar to bones and teeth. They have the ability to be partially dissolved, and so allow cells to proliferate in their place. However, such property is not suitable for dental applications as it promotes teeth dissolution even when tooth enamel cells do not regenerate. Furthermore, much of the commercially available apatite is currently produced through chemical synthesis, making the product expensive and technology dependent. Fluorapatite is known to be the harder and more insoluble alternative. It promotes re-mineralization and is said to have anti-microbial properties. In addition, the mineral occurs in certain brachiopod shells found in the country. They are called Balay in Visayas. Fluorapatite was successfully extracted and characterized from these locally available shells. Protein analysis yielded an excellent degree of organic matter removal, while FTIR and XRD verified the extraction and purity of the obtained fluorapatite powder. Pellets made through pressing and sintering showed that it is also formable and compatible with current dental material fabrication techniques. The sintered pellets passed the ISO standards for dissolution of dental restoratives. In addition, the compression loading test and Vickers indentation showed that the milling time played a role in the resulting mechanical properties. Thus, to bring out these desired properties, one only needed to optimize the fabrication parameters. This study proves the viability of fluorapatite from brachiopod shells as an alternative biomaterial.
Keywords: Dental materials; Fourier transform infrared spectroscopy; Brachiopod shells